Normative data and factorial structure of the Turkish version of the temperament and character inventory-revised (Turkish TCI-R) - Samet Kose; Mehmet Yalcin; Ercan Akin; Hakan Turkcapar (Psychiatry and Clinical Psychopharmacology, 2019)
OBJECTIVE In this study, we aimed to examine the validity, reliability, and factor structure of the TCI-R in a Turkish sample. METHODS Participants were 1026 (786 female, 240 male) college students at Hasan Kalyoncu University in Turkey. The study protocol was approved by the local Ethics Committee. Sociodemographic information of the participants was collected and the TCI-R, Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), and Personality Belief Questionnaire (PBQ) were administered. All statistical analyses were performed by using SPSS version 24 for Windows. RESULTS The internal consistency was satisfactory for all dimensions (Cronbach alpha coefficients above 0.7). The highest Cronbach alpha was found for Persistence Dimension (0.92) and the lowest Cronbach alpha was found for Novelty Seeking Dimension (0.73) and test–retest correlation coefficients for all dimensions were relatively high and statistically significant. TCI-R temperament and character scales were found significantly correlated with the BDI, the BAI, and the PBQ total scores. A principal-components analysis with Promax rotation yielded four factors with an Eigenvalue greater than one, representing 62.67% of the total variance for temperament dimension. A principal-components analysis with Promax rotation yielded three factors with an Eigenvalue greater than one, representing 56.14% of the total variance for character dimension. The addition of four new subscales to the original scale for Persistence has produced a very reliable dimension in the TCI-R with the loadings ranging from 0.82 to 0.86. CONCLUSIONS Our findings suggested that Turkish TCI-R was a valid and reliable tool with a robust factorial structure for further use in the assessing of personality psychopathology in clinical populations in Turkey.